2014
DOI: 10.1007/s10067-014-2703-2
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in total ankle arthroplasty in the USA: a study of the National Inpatient Sample

Abstract: Objective To assess the time-trends in utilization, clinical characteristics and outcomes of patients undergoing total ankle arthroplasty (TAA) in the U.S. Methods We used the Nationwide Inpatient Sample (NIS) data from 1998 to 2010 to examine time-trends in the utilization rates of TAA. We used the Cochran Armitage test for trend to assess time-trends across the years and the analysis of variance (ANOVA), Wilcoxon test or chi-squared test (as appropriate) to compare the first (1998–2000) and the last time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 26 publications
(29 reference statements)
1
78
2
Order By: Relevance
“…This increase in foot and ankle arthrodesis, particularly in the ambulatory setting, likely reflects advancements in surgical techniques, including those of arthroscopy and fixation, an expanding set of surgical indications (2), and improvements in regional anesthesia. Interestingly, the increase in alternative treatments such as total ankle replacement (43)(44)(45) has not resulted in a decreased population-adjusted rate of arthrodesis (46).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in foot and ankle arthrodesis, particularly in the ambulatory setting, likely reflects advancements in surgical techniques, including those of arthroscopy and fixation, an expanding set of surgical indications (2), and improvements in regional anesthesia. Interestingly, the increase in alternative treatments such as total ankle replacement (43)(44)(45) has not resulted in a decreased population-adjusted rate of arthrodesis (46).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies from Australia, New Zealand, the United Kingdom, France, and the United States demonstrated that the percentage of RA was less than or around 10 % [6, 19, 21, 24]. A previous study from the United States demonstrated a decrease in the percentage of RA from 10.8 % in 1998–2000 to 4.9 % in 2009–2010 [2]. This trend could indicate that growing evidence of good clinical outcomes after TAA has been expanding the indication for TAA from low-activity patients such as those with RA to higher-level activity patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report using the United States Nationwide Inpatient Sample data contained data from five to eight million hospital stays and discharges from > 1,000 hospitals sampled to approximate a 20 % stratified sample of United States community hospitals. This sample showed an approximately 6-fold increase in TAA utilization in the previous decade, from 0.13 per 100,000 population in 1998 to 0.84 per 100,000 population in 2010 [2]. Another study from the United States using the Medicare database included 5871 patients who underwent TAA and 29532 patients who underwent ankle arthrodesis between 1991 and 2010; this study reported an increase in TAA volume from 72 procedures in 1991 to 888 in 2010 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of TAA has brought awareness of potential complications associated with ankle arthroplasty. 4,5 Two of the most significant complications of TAA that have the greatest impacts on quality of life and patient function outcomes include postoperative wound breakdown and infection. [6][7][8] Dehiscence for the anterior approach incision is the most common soft tissue complications following TAA, with reports of 8.5% to 28% of patients after ankle arthroplasty.…”
mentioning
confidence: 99%
“…6,7,9 Though the anterior incision offers convenient access to the ankle joint, this incisional approach can lead to vascular damage, causing wound healing issues, dehiscence, and necrosis of bony and soft tissues. 5,6,8 Minor wounds, small dehiscence, and superficial infections can quickly seed into deeper tissues, increasing risk of hardware removal and excision of infected tissue.…”
mentioning
confidence: 99%